The Relation of Optimism to Relative Telomere Length in Older Men and Women. Issue 2 (February 2020) - Kim, Eric S.; Tindle, Hilary A.; Kubzansky, Laura D.; Liu, Simin; Duncan, Meredith S.; Manson, JoAnn E.; Springfield, Sparkle; Salmoirago-Blotcher, Elena; Shadyab, Aladdin H.; Liu, Buyun; Grodstein, Francine; De Vivo, Immaculata
ABSTRACT: Objective: Mounting evidence suggests that higher optimism is associated with reduced risk of age-related morbidities and premature mortality. However, possible biological mechanisms underlying these associations remain understudied. One hypothesized mechanism is a slower rate of cellular aging, which in turn delays age-related declines in health. Methods: We used data from two large cohort studies to test the hypothesis that higher optimism is associated with longer leukocyte telomere length. With cross-sectional data from the Health and Retirement Study (HRS; n = 6417; mean age = 70 years) and the Women's Health Initiative (WHI; N = 3582; mean age = 63 years), we used linear regression models to examine the association of optimism with relative telomere length (assessed in leukocytes from saliva [HRS] or plasma [WHI]). Models adjusted for sociodemographics, depression, health status, and health behaviors. Results: Considering both optimism and telomere length as continuous variables, we found consistently null associations in both cohorts, regardless of which covariates were included in the models. In models adjusting for demographics, depression, comorbidities, and health behaviors, optimism was not associated with mean relative telomere length (HRS: β = −0.002, 95% confidence interval = −0.014 to 0.011; WHI: β = −0.004, 95% confidence interval = −0.017 to 0.009). Conclusions: Findings do not support mean telomere length as a mechanism that explains observed relations of optimism with reduced risk of chronic disease in older adults. Future research is needed to evaluate other potential biological markers and pathways. Abstract : Supplemental digital content is available in the text.